Illustrating a case by using diagrams: Development of social inclusion of people with Down syndrome in Malaysia - Md Romainoor, Nurul Hanim (Curtin University, 2013)
Objective: To illustrate the development of social inclusion of people with Down syndrome in Malaysia by using diagrammatic form. Methods: In-depth qualitative analysis. Results: There is a need to have systematic process to understand complex disability issues in the uncertainty Malaysia. Illustrating opinions and analysis in a diagrammatic form is to explain the complex details. Conclusions: The complex interrelated challenges were expressed through structural visual models which can be used by stakeholders.